2020
DOI: 10.21203/rs.3.rs-19693/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic deletion of microRNA-22 blunts the inflammatory transcriptional response to status epilepticus and exacerbates epilepsy in mice

Abstract: MicroRNAs perform important roles in the post-transcriptional regulation of gene expression. Sequencing as well as functional studies using antisense oligonucleotides, indicate important roles for microRNAs during the development of epilepsy through targeting transcripts involved in neuronal structure, gliosis and inflammation. MicroRNA-22 (miR-22) has been reported to protect against the development of epileptogenic brain networks through suppression of neuroinflammatory signalling. Here, we used mice with a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…The time-dependent role of peripheral EP2 receptor signaling after status epilepticus is another important factor in understanding the contributions of peripheral inflammation to its detrimental effect on overall health. In fact, early neuroinflammation after status epilepticus may be neuroprotective, 9 and Dingledine and colleagues have previously shown that there are distinct therapeutic windows for Cox-2 inhibition following status epilepticus. 10 As a next step, inducible myeloid cellspecific EP2 receptor knockout mice could be used to identify the most beneficial time window to block peripheral EP2 signaling for improvement of recovery after status epilepticus.…”
Section: Commentarymentioning
confidence: 99%
“…The time-dependent role of peripheral EP2 receptor signaling after status epilepticus is another important factor in understanding the contributions of peripheral inflammation to its detrimental effect on overall health. In fact, early neuroinflammation after status epilepticus may be neuroprotective, 9 and Dingledine and colleagues have previously shown that there are distinct therapeutic windows for Cox-2 inhibition following status epilepticus. 10 As a next step, inducible myeloid cellspecific EP2 receptor knockout mice could be used to identify the most beneficial time window to block peripheral EP2 signaling for improvement of recovery after status epilepticus.…”
Section: Commentarymentioning
confidence: 99%